2020
DOI: 10.1177/2516103220908043
|View full text |Cite
|
Sign up to set email alerts
|

Exploring links between early adversities and later outcomes for children adopted from care: Implications for planning post adoption support

Abstract: This study explored how child maltreatment, alongside a range of other variables, predicted adverse outcomes for children adopted from the foster care system in England. The participants were 319 adoptive parents who completed an in-depth online survey about their most recently adopted child. The mean age of children at placement for adoption was 28 months (range 0–11 years) and their ages at the time of the survey ranged from 0 years to 17 years (mean = 7 years). Detailed information was collected about child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(63 reference statements)
2
7
0
Order By: Relevance
“…These findings are consistent with studies which asked adoptive parents about their child's maltreatment (e.g. Neil et al, 2020) and used case file approaches (Kim, Wildeman, Jonson-Reid & Drake, 2017). In addition to maltreatment, around a third of our sample was exposed to domestic violence and/or a parent who abused drugs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are consistent with studies which asked adoptive parents about their child's maltreatment (e.g. Neil et al, 2020) and used case file approaches (Kim, Wildeman, Jonson-Reid & Drake, 2017). In addition to maltreatment, around a third of our sample was exposed to domestic violence and/or a parent who abused drugs.…”
Section: Discussionsupporting
confidence: 90%
“…A study of German children adopted from care (international and domestic) found that psychosocial adjustment was significantly predicted by pre-adoptive risk factors, including pre-natal risk factors and maltreatment/neglect (Hornfeck et al, 2019). A recent study of children adopted from the foster care system in England found that children with exposure to drugs or alcohol in utero, parental learning difficulties, and adverse experiences between birth and moving to the adoptive family was associated with poorer child behavior, wellbeing and relationship quality (Neil, Morciano, Young, & Hartley, 2020).…”
Section: Childhood Adversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the lack of epidemiological data for the mental health and well-being needs of adopted children makes service delivery and innovations difficult to implement and to evaluate. However, the sample demographics presented here are similar to the Adoption UK 'State of the Nation' (Adoption UK, 2019) as well recent large samples of UK adopters (e.g., Neil et al, 2020), which suggest this sample is not a profoundly different group from UK adopters in general. What we have shown is that for adoptive parents who had had contact with CAMHS, they had significant mental health concerns about their children, their concerns were wide-ranging, and certainly not restricted only to issues of attachment and trauma, and when these families had accessed CAMHS they had been deeply dissatisfied.…”
Section: Discussionsupporting
confidence: 56%
“…the child having a recorded disability, as a recent report suggested that the 'Adverse Childhood Experiences' framework ignores other sources of adversity, including disability (Welsh Government, 2021); and parental learning difficulties associated with lower child well-being (Neil et al, 2020). See Table 1 for adversity definitions.…”
Section: Key Messagesmentioning
confidence: 99%